2003
DOI: 10.4315/0362-028x-66.12.2355
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ozone To Reduce Molds in a Cheese Ripening Room

Abstract: Cheese ripening rooms have an unusual environment, an environment that encourages mold growth. Ozone has been applied in various ways in the food industry. One useful advantage of ozone is that it inactivates molds. In this study, a cheese ripening room was ozonated, and the effectiveness of this treatment was evaluated both in air and on surfaces through sampling on a weekly basis over a 3-month period. The results obtained indicate that ozone treatment reduced the viable airborne mold load but did not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 7 publications
4
32
0
6
Order By: Relevance
“…Os fungos são contaminantes comuns em alimentos e são responsáveis por perdas financeiras industriais e comerciais (SERRA et al, 2003). A ozonização é bastante efetiva contra fungos e micotoxinas, porém os fungos tendem a ser mais resistentes que as bactérias na forma vegetativa (RUSSEL; HUGO; AVLIFFE, 1999; KIM; YOUSEF; DAVE, 1999).…”
Section: Ação Sobre Os Fungosunclassified
See 1 more Smart Citation
“…Os fungos são contaminantes comuns em alimentos e são responsáveis por perdas financeiras industriais e comerciais (SERRA et al, 2003). A ozonização é bastante efetiva contra fungos e micotoxinas, porém os fungos tendem a ser mais resistentes que as bactérias na forma vegetativa (RUSSEL; HUGO; AVLIFFE, 1999; KIM; YOUSEF; DAVE, 1999).…”
Section: Ação Sobre Os Fungosunclassified
“…Em uvas houve redução do apodrecimento fúngico com tratamento de ozônio e armazenamento a frio (KIM; YOUSEF; DAVE, 1999). Serra et al (2003) utilizaram ozônio em uma câmara de maturação de queijos, mantida a 5 °C e umidade relativa até 80% durante 3 meses. Os autores empregaram uma taxa de geração de ozônio de 8 g/h nos primeiros 5 dias, seguida por 4 g/h nos próximos 5 dias e 8 g/h a cada 40 min por período de uma hora durante o restante da maturação.…”
Section: Aplicação Do Ozônio No Processamento De Alimentosunclassified
“…Najafi and Khodaparast (2009) showed that Escherichia coli and Staphylococcus aureus could not be cultured in date fruits following treatment with 5 ppm ozone for 60 min. Serra et al (2003) used ozone to reduce molds to below the level of 50 MPN/m 3 in a cheese ripening room over a 3-month period. Ozone has proven to be an effective method to inactivate molds in a closed space.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases the efficacy of ozone was not sufficient, e.g. against moulds on surfaces [3] or for the complete decontamination of the surface of eggs inoculated with Salmonella enteritidis bacteria [2]. Of the strains tested, gram-negative rods of E. coli and P. aeruginosa were the most sensitive, a finding also presented by others [e.g.…”
Section: Discussionmentioning
confidence: 58%
“…Results on the efficacy of ozone on bacteria and moulds in ambient air have already been published [3,4]. Higher concentrations of ozone acting for a shorter time (4 and 20 ppm, 10-480 min.)…”
Section: Discussionmentioning
confidence: 97%